Short Communication Status of Grain Smut Sphacelotheca sorghi and Long Smut Tolyposporium ehrenbergii of Sorghum in Sindh and Balochistan, Pakistan (Biological Sciences - PJSIR, 2005)
Survey of various parts of Sindh and Balochistan was conducted to determine the presence and distribution of Sphacelotheca sorghi, the causal organism of grain smut of sorghum. The percentage of disease in different localities of Sindh was 2% in Dadu, 0.5% in Piyaro Goth, 3% in Mehar, 3% in Nasirabad, 4% in Larkana, 8% in Kamber, 4% in Shahdadkot, 5% in Jacobabad, 5% in Thull, 6% in Kandhkot, 7% in Lakhi, 7.5% in Jehan Khan, 8.3% in Sukkur, 20% in Rohri, 15% in Ghotki, 15% in Mirpurmathelo, 15% in Ubaro, 20% in Daherki, 20.5% in Khairpur (Mir) and 17.1% in Karoondhi, and in localities of Balochistan was 7% in Nasirabad and in 7% Usta Mohammad. The incidence of long smut, Tolyposporium ehrenbergii, in Sindh was recorded at 0.2% in Dadu, 0.1% in Piyaro Goth, 0.5% in Mehar, 0.03% in Nasirabad, 0.6% in Larkana, 0.3% in Kamber, 1% in Shahdadkot, 1.2% in Jacobabad, 1.5% in Thull, 1.1% in Kandhkot, 1% in Lakhi, 1.3% in Jehan Khan, 1.5% in Sukkur, 3.5% in Rohri, 5% in Ghotki, 8.1% in Mirpurmathelo, 7.5% in Ubaro, 8.9% in Daherki, 9.1% in Khairpur (Mir) and 8% in Kroondhi, and in Balochistan was1.3% in Nasirabad and 1.4% in Usta Mohammad